Stability of complete Blood Count in different storage conditions using the automated hematological analyzers - سالم, سناء; تغريد قدّار,; فراس حسين , (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: Complete blood count is routine hematological test used to assess natural and pathological alterations and monitoring therapy, therefore we report the effects of storage temperature and duration on complete blood count results. Methods: We measured complete blood count in 202 blood samples within hour after blood collection (baseline) and after (4, 24, 48 and 72) hours of storage at room temperature and 4°c. The test is performed on Medonic M20 Basic analyzer. The imprecision of the results was evaluated by the analytical coefficient of variation (CVa%) obtained by the typical error (TE) and by ANOVA analysis, to compare the averages. The reliability of results was evaluated by the CVa (%) within the maximum allowable analytical variation and by the difference of means in relation to the baseline sample (1 hour). Results: MCH is the only parameter that showed stability up to 72 hours at room temperature and at 4°C. The other complete blood count parameters showed imprecised results emitted by the Medonic M20 Basic from 4 hours of sample storage, independent of storage temperature. In addition, there were significant oscillations in the mean values of hematocrit, MCV, MCHC, RDW, platelets count and MPV, particularly for samples stored at room temperature, with the exception of platelet parameters that also exhibited mean changes at 4°C. Conclusion: The results demonstrate the importance of clinical analyst’s knowledge about the behavior of CBC parameters over time under different storage conditions, for the suitable interpretation of results.